2003
DOI: 10.1523/jneurosci.23-16-06399.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aPax6-Dependent Epidermal Growth Factor Family Signaling Source at the Lateral Edge of the Embryonic Cerebral Cortex

Abstract: In an emerging model, area patterning of the mammalian cerebral cortex is regulated in part by embryonic signaling centers. Two have been identified: an anterior telencephalic source of fibroblast growth factors and the cortical hem, a medial structure expressing winglessint (WNT) and bone morphogenetic proteins. We describe a third signaling source, positioned as a mirror image of the cortical hem, along the lateral margin of the cortical primordium. The cortical antihem is identified by gene expression for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 46 publications
(36 reference statements)
8
155
0
6
Order By: Relevance
“…Several studies indicate that the dLGE, together with the VP and LP, shows the strongest phenotype in the absence of functional Pax6: Mash1, Dlx1,2, and Gsh2, which are normally restricted to the MGE and LGE neuroepithelium, spread dorsally into VP-LP, whereas VP-LP markers Ngn2, Tbr1, and Lhx2 are almost eliminated at the PSB (Stoykova et al, 1996(Stoykova et al, , 2000Toresson et al, 2000;Yun et al, 2001;Muzio et al, 2002). Rather than being shifted dorsally, the VP in the Pax6 mutant appears to be defective, based on the absence of VPspecific markers sFrp2 and Dbx1 (Kim et al, 2001;Yun et al, 2001;Assimacopoulos et al, 2003). A deficient VP in the Tlx mutant has been correlated with disrupted La and BL development (Stenman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that the dLGE, together with the VP and LP, shows the strongest phenotype in the absence of functional Pax6: Mash1, Dlx1,2, and Gsh2, which are normally restricted to the MGE and LGE neuroepithelium, spread dorsally into VP-LP, whereas VP-LP markers Ngn2, Tbr1, and Lhx2 are almost eliminated at the PSB (Stoykova et al, 1996(Stoykova et al, , 2000Toresson et al, 2000;Yun et al, 2001;Muzio et al, 2002). Rather than being shifted dorsally, the VP in the Pax6 mutant appears to be defective, based on the absence of VPspecific markers sFrp2 and Dbx1 (Kim et al, 2001;Yun et al, 2001;Assimacopoulos et al, 2003). A deficient VP in the Tlx mutant has been correlated with disrupted La and BL development (Stenman et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the CGE also contains the caudal prolongations of the pallial territories that are also found rostrally in the most dorsal aspect of the LGE and immediately adjacent to it. These pallial components are characterized by the expression of Dbx1, Fgf7, Sfrp2, and Pax6 (and several other markers) and the lack of Emx1 at early development stages (Smith-Fernández et al, 1998;Puelles et al, 2000;Kim et al, 2001;Assimacopoulos et al, 2003;Medina et al, 2004). Because pallial, LGE, and MGE domains are organized concentrically in the telencephalic hemispheres (Puelles et al, 2000), the CGE contains progressively less progenitor pools as it extends caudally, until eventually the most caudal CGE appears to only consist of pallial progenitors (Kim et al, 2001, their Fig.…”
Section: The Cge Contains the Caudal Extension Of Lge And Mge Progenimentioning
confidence: 99%
“…During embryogenesis, cells of the LCS emerge from the "molecular" corticostriatal border (CSB), the region of the dorsal LGE (dLGE) in which pallial gene expression [e.g., Pax6 (paired box gene 6) and Ngn2 (neurogenin homolog 2)] abuts subpallial gene expression [e.g., Gsh2 (genomic screened homeobox 2) and Dlx1/2 (distal-less homeobox 2) (for review, see Corbin et al, 2001; Molnár and Butler, 2002)]. This "molecular" CSB (herein referred to as CSB) is po-sitioned just ventral to the corticostriatal sulcus and also is the site of expression of a variety of specific intrinsic [e.g., Dbx1 (developing brain homeobox 1), Er81 (Ets transcription factor ER81), Sp8 (a member of the Sp1 zinc finger transcription factor gene family), and Tsh1 (Teashirt 1)] and extrinsic [e.g., Sfrp2 (secreted frizzled-related protein 2), Tgf-␣, and Fgf7] factors (Lu et al, 1996;Kim et al, 2001;Assimacopoulos et al, 2003;Stenman et al, 2003a;Caubit et al, 2005;Waclaw et al, 2006). Furthermore, gene expression studies have indicated that the LCS consists of at least two progenitor populations that arise from both the pallial and subpallial compartments (Stoykova et al, 1996;Puelles et al, 2000;Toresson et al, 2000;Yun et al, 2001;Medina et al, 2004;Tole et al, 2005).…”
Section: Introductionmentioning
confidence: 99%